2023
DOI: 10.4236/odem.2023.111004
|View full text |Cite
|
Sign up to set email alerts
|

Automobile Pollution and Risk of Impaired Lung Function and Oxygen Saturation among Vendors Near Road Traffic in Brazzaville, Congo

Abstract: Context: Automobile pollution is becoming a potential threat to the cardiorespiratory health of the urban population of sub-Saharan Africa. The present study aims to evaluate the level of concentrations of fine particles (PM2.5 and PM10) near road traffic and the effects of exposure to automobile pollutants on pulmonary function and arteriolar blood oxygen saturation among sellers around road traffic. Materials and Methods: The study recruited 48 healthy people carrying out a sales activity near road traffic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The various analyses carried out have made it possible to find a significant association between exposure to suspended particles and mortality from natural causes, cardiovascular morbidity and mortality, particularly in terms of coronary events and morbidity of the respiratory system [18] [19]. The same results were reported by [10]. Both animal and human epidemiological studies support the idea that atmospheric pollutants cause abnormalities during gametogenesis leading to a decrease in the reproductive capacities of exposed populations.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The various analyses carried out have made it possible to find a significant association between exposure to suspended particles and mortality from natural causes, cardiovascular morbidity and mortality, particularly in terms of coronary events and morbidity of the respiratory system [18] [19]. The same results were reported by [10]. Both animal and human epidemiological studies support the idea that atmospheric pollutants cause abnormalities during gametogenesis leading to a decrease in the reproductive capacities of exposed populations.…”
Section: Discussionmentioning
confidence: 72%
“…About developing countries, serious problems of air pollution exist mainly in large cities. Some limited studies have been carried out in the urban areas recently to assess the effects of vehicles on ambient air quality [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological, clinical, and toxicological studies have shown an association between the appearance of non-communicable diseases and short-or long-term exposure to air pollution [2]. So-called air pollution has been associated with respiratory and cardiovascular pathologies, including myocardial infarction, heart failure, high blood pressure, and strokes [3] [4] [5]. At the same time, epidemiological studies have described the involvement of air pollution in neurodevelopmental disorders and neurodegenerative diseases such as Parkinson's disease and Alzheimer's, as well as in bronchial, bladder, and breast cancers [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%